Strategi Analisis Displin Siswa dengan Konseling Individu Teknik Behavioral Contract - Ariana Pangastuti; Muhammad Yuliansyah; Muhammad Eka Prasetia (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2020)
In order for students to improve their discipline, the Behavioral Contract technique provides individual counseling services. The research aims to find out how it is implemented, the obstacles and the factors causing the late students of SMAN 4 Banjarmasin. Method using qualitative. With the background of students with the initials SNA, R, MI and SR. The results of the research after being provided with student services were not late for school to become disciplined. Research is expected to add insight into the field of counseling guidance, enrich the theory, especially with regard to discipline late entering school. Keywords: Discipline; Late School Entry; Individual Counseling; Behavioral Contracts